The Columbia-suicide severity rating scale: validity and psychometric properties of an online Spanish-language version in a Mexican population sample - Austria-Corrales, Fernando; Jiménez-Tapia, Alberto; Astudillo-García, Claudia Iveth; Arenas-Landgrave, Paulina; Xochihua-Tlecuitl, Tonatiuh; Cruz-Cruz, Copytzy; Rivera-Rivera, Leonor; Gómez-García, José Alberto; Palacios-Hernández, Bruma; Pérez-Amezcua, Berenice; Toledano-Toledano, Filiberto; Richards, Jenelle; et al. (Frontiers in Public Health, 2023)
The aim of this study was to evaluate the validity and psychometric properties in a Mexican sample of a Spanish-language online version of the Columbia-Suicide Severity Rating Scale (C-SSRS). Data were collected between May and October 2021 from 3,645 participants aged 18 years and over, who agreed to complete the questionnaire. Reliability analysis, confirmatory factor analysis (CFA), and psychometric properties were calculated using a two-parameter model. The results showed a reasonable level of reliability with a Cronbach's alpha of 0.814, and evidence of unidimensionality, and construct validity for suicide risk at three risk levels: low, medium, and high. Analysis of the items suggests that they are consistent with the proposed theoretical model. Our results also demonstrate that the parameters are stable and able to efficiently discriminate individuals at high risk of suicide. We propose the use of this version of the C-SSRS in the Spanish-speaking population, since it is a multifactorial assessment of suicide risk and the inclusion of other clinical and risk factor assessments for a more comprehensive evaluation.